Pengetahuan Dan Sikap Remaja Awal Puteri Dalam Menghadapi Menarche Di Sd Negeri Kaluku Bodoa Makassar - Andi Syintha Ida; Rismawati Basri; Zulaeha A. Amdadi (Politeknik Kesehatan Makassar, 2021)
Abstract Menarche is something that happens to all healthy and non-pregnant Daughters teenagers as a sign of maturity. Early adolescent approaches and counseling from families, parents and teachers and health workers are very useful and able to provide lessons and education to young women so that they are better prepared for their puberty. This study aims to determine whether there is a relationship between knowledge with early adolescent girls attitude in facing menarche in SD Negeri Kaluku Bodoa Makassar. Samples were taken from All Grade VI students, with the total sample being 36 persons. The type of research used is correlational research with cross sectional approach. Sampling using total sampling technique. So it is concluded that there is a meaningful relationship between Knowledge with the attitude of early teenagers in the face of menarche. It is therefore advisable to the relevant Institutions to teach students early on about reproduction health education or to cooperate with health workers to conduct routine counseling about reproduction organ health in schools so that students better understand and understand about the importance of maintaining their reproductive organs. Keywords : Attitude, Knowledge, , Menarche.